2015
DOI: 10.1021/acs.jpclett.5b01488
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Potential Stabilization of Reconstructed Au(111) Structure by Monolayer Coverage with Graphene

Abstract: The electrochemical properties of a monolayer graphene grown on a Au(111) electrode were studied using cyclic voltammetry (CV) and electrochemical scanning tunneling microscopy (EC-STM). CV and EC-STM measurements in 0.1 M H2SO4 aqueous solution revealed that graphene grown on the reconstructed (22 × √3) Au(111) structure effectively inhibited potential-induced structural transitions between reconstructed (22 × √3) and unreconstructed (1 × 1), and the adsorption/desorption of SO4(2-) ions, which are intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…1. The interpretation of the voltammetric feature of Au(111) has been reported before [17][18][19] In a highly acidic electrolyte (0 < pH < 1), the main species of antimony is SbO + as reported by Wu et al [9]. The following small peak C2 (~ +0.28 V) is due to the reduction of oxygenous Sb(III) species from bulk solution.…”
Section: Chemicals Materials and Electrolytesupporting
confidence: 53%
“…1. The interpretation of the voltammetric feature of Au(111) has been reported before [17][18][19] In a highly acidic electrolyte (0 < pH < 1), the main species of antimony is SbO + as reported by Wu et al [9]. The following small peak C2 (~ +0.28 V) is due to the reduction of oxygenous Sb(III) species from bulk solution.…”
Section: Chemicals Materials and Electrolytesupporting
confidence: 53%
“…MoS 2 and MoSe 2 monolayers were grown on Au(111) surfaces by chemical vapor deposition. Figure a shows a representative optical image of a Au bead with a (111)‐facet surface produced by the method of Clavilier et al, which is a commonly used technique for obtaining an atomically flat Au crystal surface . As indicated by the white dotted circles, sub‐millimeter (111) crystal surfaces can be produced on the Au bead.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1a shows a representative optical image of a Au bead with a (111)-facet surface produced by the method of Clavilier et al, [16] which is a commonly used technique for obtaining an atomically flat Au crystal surface. [17] As indicated by the white dotted circles, sub-millimeter (111) crystal surfaces can be produced on the Au bead. STM measurements confirmed a herringbone Au(111) reconstructed pattern on large terrace and a hexagonal lattice structure with a lattice constant of 0.29 nm, corresponding to the interatomic spacing of the Au(111) lattice (0.288 nm).…”
Section: Resultsmentioning
confidence: 99%
“…This also supports the general procedure of Pt single crystal annealing under Ar/CO atmosphere, allowing for new insights in the underlying mechanisms of step mobility and stability. In a recent work of Yasuda et al, the focus was shifted toward stabilizing reconstructed surfaces, specifically the reconstructed Au(111), by adding a monolayer of graphene by atmospheric pressure chemical vapor deposition . The authors concluded that both a protection from the double layer and from anion adsorption shielded the gold surface and maintained its stability over a wide potential range (up to +1.35 V vs Ag/AgCl (saturated KCl)) and even over an extended period of time.…”
Section: Imaging Of Catalyst Surface Structurementioning
confidence: 99%